ChemInform Abstract: Docking Studies, Synthesis, Characterization of Some Novel Oxazine Substituted 9‐Anilinoacridine Derivatives and Evaluation for Their Antioxidant and Anticancer Activities as Topoisomerase II Inhibitors. Issue 13 (18th March 2013) - Kalirajan, R.; Kulshrestha, Vivek; Sankar, S.; Jubie, S.
Abstract Novel acridine derivatives (IIIa) and (IIIc)—(IIIe) have significant anticancer activity against Daltons Lymphoma Ascites (DLA) cells.